The influence of antiresorptive bone medication on the effect of high-intensity resistance and impact training on osteoporotic fracture risk in postmenopausal women with low bone mass: protocol for the MEDEX-OP randomised controlled trial - Melanie Fischbacher; Benjamin K Weeks; Belinda R Beck (BMJ Open)
Introduction Antiresorptive medications increase bone density and decrease vertebral fracture, while high-intensity resistance and impact training (HiRIT) increases balance, bone and muscle strength decreasing risk for falls and fractures. Medications are typically prescribed by doctors and exercise by exercise specialists, frequently in isolation.Objective Our primary aim is to determine the effect of an 8-month HiRIT programme with or without osteoporosis medications on bone mineral density (BMD) of the spine and hip in postmenopausal women with low bone mass.Methods and analysis One hundred and sixty postmenopausal women with low bone mass will be recruited from the community to participate in an 8-month randomised controlled trial. Participants will be on stable doses of antiresorptive bone medication for at least 12 months (n=80) or have not taken bone medications for at least 12 months (n=80). Participants will be block randomised, stratified by medication intake, to twice-weekly 40-min supervised sessions of HiRIT or a low-intensity exercise programme (control). Primary outcomes include change in lumbar spine and total hip areal bone mineral density. Secondary outcomes include whole body, femoral neck and forearm BMD, proximal femur bone geometry and volumetric density, vertebral morphology, body composition, anthropometry, physical function, posture, rate of falls, osteoarthritis symptoms, pelvic floor health, quality of life, physical activity enjoyment, resting blood pressure, safety and compliance. All outcomes will be assessed at baseline and 8 months and intention-to-treat and per-protocol analyses will be conducted. Repeated measure analysis of covariance will be used to determine intervention effects on outcome measures, controlling for initial values, compliance and other variables found to differ between groups at baseline.Ethics and dissemination The study has been approved by Griffith University Human Research Ethics Committee (Ref: 2017/739). Results will be reported in peer-reviewed journals and at conferences.Trial registration number Australian New Zealand Clinical Trials Registry (ACTRN12617001511325).